2018
DOI: 10.3390/ijerph15030435
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characteristics of Cataract Surgery in Poland, during 2010–2015

Abstract: Background: To assess the incidence and characteristic of cataract surgery in Poland from 2010 to 2015 and to interpret these findings. Patients and methods: Data from all patients who underwent cataract surgery alone or in combined procedures in Poland between January 2010 and December 2015 were evaluated. Patient data were from the national database of hospitalizations maintained by National Health Fund. Data on the population of Poland were obtained from Central Statistical Office of Poland. Results: In tot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…We analyzed the surgical characteristic of cataract surgery in Poland to find the possible explanation for the acute and chronic POE decrease over the years. We found that during the study period the total number of one-day cataract surgeries significantly increased, while the use of extracapsular lens extraction significantly decreased [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the surgical characteristic of cataract surgery in Poland to find the possible explanation for the acute and chronic POE decrease over the years. We found that during the study period the total number of one-day cataract surgeries significantly increased, while the use of extracapsular lens extraction significantly decreased [10].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to assess the incidence and characteristic of endophthalmitis after cataract surgery in the overall population of Poland from 2010 to 2015. Our study was part of a project titled “Maps of Healthcare Needs—Database of Systemic and Implementation Analyses,” which was co-financed by the European Union funds through the European Social Fund under the Operational Program Knowledge, Education, and Development [10].…”
Section: Introductionmentioning
confidence: 99%
“…The present study was a part of the Polish Ministry of Health project “Maps of Healthcare Needs—Database of Systemic and Implementation Analyses” and was co-financed by the European Union funds through the European Social Fund under the Operational Program of Knowledge Education and Development (EU grant number: POWR 05.02.00-00-0149/15-01) [ 12 , 13 , 14 ]. The study design was a retrospective and nationwide survey.…”
Section: Methodsmentioning
confidence: 99%
“…The present study was co-financed by the European Union funds through the European Social Fund under the Operational Program of Knowledge, Education, and Development and was a part of the Polish Ministry of Health project “Maps of Healthcare Needs —Database of Systemic and Implementation Analyses” [ 15 , 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%